Enrichment of novel CD3+F4/80+ cells in brown adipose tissue following adrenergic stimulation - Chae, Hee-Don; Levi, Jelena (Frontiers in Immunology, 2024)
Macrophages play a multifaceted role in maintaining tissue homeostasis, fighting infections, and regulating cold-induced thermogenesis. The brown adipose tissue (BAT) is crucial for maintaining body temperature during cold exposure. Cold stress triggers the sympathetic nervous system to release norepinephrine (NE), which activates BAT via β3-adrenergic receptors, initiating lipolysis and glycolysis. BAT-infiltrating macrophages can either hinder or enhance thermogenesis by controlling the interplay between BAT cells and sympathetic nerves. In this study we report on a unique population of CD3+F4/80+ dual lineage co-expressing (DE) cells within the interscapular BAT (iBAT), that increased following chronic adrenergic stimulation. In forward scatter/side scatter plots, they formed clusters distinct from lymphocytes, appearing larger and more complex. These CD3+F4/80+ DE cells demonstrated the lack of T cell markers CD62L and TCRβ and expressed higher levels of Ly6C, F4/80, and CD11b markers compared to T cells and CD3-macrophages. Furthermore, analysis revealed two subpopulations within the CD3+F4/80+ DE population based on MHCII expression, with the proportion of MHCII-low subset increasing with adrenergic stimulation. This novel DE population within iBAT, unequivocally identified by the its unique surface marker profile, warrants further investigation into the intricate mechanisms governing adaptive thermogenesis regulation.